Sustainable urban forms in the Arabian Gulf: an evidence-based analysis of Kuwaiti social housing neighborhoods at Jaber Al-Ahmed City - Al-Ansari, Mae; AlKhaled, Saud (Frontiers in Built Environment, 2023)
In September 2015, the State of Kuwait signed the UN’s 2030 Agenda, committing to all 17 of its Sustainable Development Goals (SDGs), which include the building of sustainable cities and communities through initiatives such as social housing. In response, the New Kuwait Vision 2035 has witnessed a shift in approach to the social housing paradigm at the state level. This paper examines the status of recent social housing projects in Jaber Al-Ahmed City, Kuwait, through a critical, evidence-based analysis of the decision-making processes and urban-architectural products that shaped its development. The mixed-methods data for this case study were generated via archival research and semi-structured interviews supplemented with field observations to evaluate the local and international sustainability agendas implemented in the city as process and product. Principles of Sustainable Urban Forms are implemented for the evaluation. The article also presents evidence of local urban practices (resident appropriation and participation), legitimized environmental practices, and community wellbeing. It concludes with recommendations for resolving issues in the current processes around the design and implementation of sustainable urban forms to inform future social housing developments. These recommendations for sustainable social housing in Kuwait provide an opportunity to revisit and reconsider the core values of sustainability while adding to the multiplicity of its definitions. Although recent social housing projects in Kuwait may demonstrate an overall effective process-to-product procedure as a means of architectural production that addresses the country’s housing demand, important aspects remain in question with regard to sustainable built environments.